Current results of surgery for achalasia of the cardia. Issue 6 (June 1993) - Emblem, R; Stringer, M D; Hall, C M; Spitz, L
Abstract : Several treatment options are available in the management of achalasia of the cardia. Of a recent series of 14 children, 12 were treated by a modified Heller's myotomy combined with a floppy Nissen fundoplication. Symptoms were dramatically improved in nine during a mean follow up period of 3.9 years. Recurrent oesophageal pain was the most resistant symptom and continued to be moderately severe in three patients, two of whom obtained temporary relief by oesophageal balloon dilatation. Two patients treated by pneumatic dilatation alone have residual symptoms. These results support a primary surgical approach to the management of achalasia in children.